Efektivitas Mediasi Sebagai Alternatif Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama Kota Palu Kelas 1A - Muh Jamal S Latimumu; Adin A; Ferdi Suko; Galuh Widyawati (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the effectiveness of mediation as an alternative for resolving sharia economic disputes in the Palu City Religious Court and to assess its compliance with PERMA Number 1 of 2016. This study uses a qualitative approach with a descriptive design and is included in the type of empirical legal research. Data were obtained through interviews, observations, and documentation, with primary data sources coming from mediator judges, court clerks, and parties who have been involved in mediation. The data analysis technique used descriptive qualitative analysis with source triangulation techniques to test the validity of the data. The results of the study indicate that the implementation of sharia economic dispute mediation in the Palu City Religious Court has generally complied with the provisions of PERMA Number 1 of 2016, both at the pre-mediation stage, the mediation process, and reporting the mediation results. The mediators also have the competence to handle sharia economic disputes as regulated in Article 13 paragraph (1) of PERMA Number 1 of 2016. However, the effectiveness of mediation is still considered less than optimal because during the 2020–2026 period there were no sharia economic dispute cases that were successfully resolved through mediation, even though there were 14 cases submitted, consisting of 8 simple lawsuits and 6 non-simple lawsuits.